Access to the Protoilludane Core by Gold-Catalyzed Allene-vinylcyclopropane Cycloisomerization - Pitaval, Anthony (American Chemical Society, 2013)
[Image: see text] Gold(I)-catalyzed allene-vinylcyclopropane cycloisomerization leads to the tricyclic framework of the protoilludanes in a single step by a reaction that involves a cyclopropane ring expansion and a Prins cyclization.